Physical activity among children with type 1 diabetes: an exploration of children’s experiences and development of an intervention to promote self-efficacy and participation - Quirk, Helen (2016)
Regular physical activity among children with Type 1 Diabetes Mellitus (T1DM) can help optimise long-term health outcomes. This thesis explores the experience of physical activity among children aged 9-11 years with T1DM and their parents, develops a physical activity intervention and evaluates its feasibility. Social cognitive theories have been drawn upon to develop our understanding and inform theoretically-driven behaviour change strategies.